2015
DOI: 10.1016/j.bbi.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Relation between acute and long-term cognitive decline after surgery: Influence of metabolic syndrome

Abstract: Introduction The relationship between persistent postoperative cognitive decline and the more common acute variety remains unknown; using data acquired in preclinical studies of postoperative cognitive decline we attempted to characterize this relationship. Methods Low capacity runner (LCR) rats, which have all the features of the metabolic syndrome, were compared postoperatively with high capacity runner (HCR) rats for memory, assessed by trace fear conditioning (TFC) on the 7th postoperative day, and learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Interestingly, cognitive decline in both cases is closely related to the hippocampus [29, 30]. TFC is a widely used method to assess learning and memory function in rodents [31]. In this study, we found that surgery induced impairment in exploratory behaviour in old C57BL/6 wild-type mice, which was accelerated by 8-hour sleep disturbance before surgery.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, cognitive decline in both cases is closely related to the hippocampus [29, 30]. TFC is a widely used method to assess learning and memory function in rodents [31]. In this study, we found that surgery induced impairment in exploratory behaviour in old C57BL/6 wild-type mice, which was accelerated by 8-hour sleep disturbance before surgery.…”
Section: Discussionmentioning
confidence: 61%
“…Hippocampal-dependent learning and memory tasks were assessed by trace fear conditioning (TFC) as previously described ( Konopka et al, 2010 ; Gambus et al, 2015 ) with minor modifications. TFC training and testing were carried out in a room with overhead fluorescent light and a ventilation fan providing background noise (65 db).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, ICR mice of 12−14 months were used to avoid failure on behavioral tests, due to age-related incompetency. Meanwhile, other studies used mice of the same age ( Gambus et al, 2015 ; Li et al, 2016 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%